The Quality of Service and Marketing Strategy to the Satisfaction and its Impact on Customer Loyalty in Mutiara Cahaya Tegal Regency - Kholipatun, Ratna Dewi; Thomas, Partono; Widiyanto, Widiyanto (Journal of Economic Education, 2018)
Today’s the competition in the retail business is very tight, so retail businesses must pay attention to the factors that can influence the development of their business. One of the factors that must be considered is customer loyalty. The objectives of this study are to determine the effect of service quality and product marketing strategy for customer satisfaction, as well as its impact on customer loyalty at Mutiara Cahaya Supermarket Tegal Regency. This study used a quantitative descriptive to explain the causality relationship between service quality and marketing strategies on customer satisfaction, and their impact on customer loyalty. The population was all Mutiara Cahaya Supermarket customers who had a member card with a total sampling of 100 people by using a incidental sampling technique. The research instrument used a questionnaire. Data analysis used multiple regression and path analysis. The results show that there is an influence of service quality and marketing strategy on customer satisfaction, there is an influence of service quality and marketing strategy on customer loyalty. The conclusion shows that there is no influence of service quality on customer loyalty through customer satisfaction, and there is an influence of marketing strategies on customer loyalty through customer satisfaction.